PEMBINAAN TENAGA DOSEN MIPA LPTK MELALUI PELATIHAN DALAM NEGERI (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 1993)
This study present a general view of inservice training dealing with the implementation of subject matter curriculum in the Teacher Education lnstitutions. The curriculum is a core curriculum developed by the Subject Mafter Team, appointed by the Directorate General of Higher Education. The training was rnainly for the matriculation program {type A} at ITB (Bandung lnstitute of Technology) and some advanced courses (type Bl. Data collected from the trainees include some studies (i.e., type of inservice training, subject matter, educational backgrounds and positionsl. A positive result is found from 700 trainees selected from 29 Teacher Education lnstitutions and who had aftended the inservice training in 5 locations/centers in both type A and Wpe B programs. However, some obstacles were found also from the trainees, dealing with differences in subject matter backgrounds and English proficiencies. The obstacles were also found in the inservice training including, the time taken for discussions and repetitions of the pre-requisite materials, and the ineffectiveness of the discussions and individual works.